IMPORTANCE OF SOCIAL CHARACTERISTIC OF COMMUNITY TO SUPPORT RESTORATION PROGRAM IN PROTECTION FOREST - Wulandari, Christine; Budiono, Pitojo; Iswandaru, Dian (Indonesian Journal of Forestry Research, 2021)
A restoration program is needed by West Lampung District, because 80% of the protected forests in this district have been damaged. Bina Wana (BW) Community Forest Group (CFG) has been successful in carrying out restoration program of 465 ha of Bukit Rigis protected forest. It resulted in an 80% increase in its members' income and an increase by 2.58% of the forest cover. To maintain the success of a sustainable restoration program, high commitment from the community is needed. This research has been conducted in June-July 2019 at West Lampung District, Lampung Province, Indonesia. The objective of this research is to analyse the social variables that affect restoration in the protection forest. The dependent variable is income and independent variables consist of respondents’ characteristics as individuals and social characteristics of the community. Based on the multiple regression linear analysis from 75 respondents, it was found that the significant variables for the sustainability of the restoration of Bukit Rigis protected forest are as follow: age, sex, education, status in CFG, distance from home to CF areas, social aids and social capital. Existence of the youth groups namely Himpunan Pemuda Peduli Hutan dan Lingkungan and Melati Women Forest Farmer Group (WFFG) plays an important role in implementing the restoration program. Establishment of HPPHL will ensure regeneration in maintaining the sustainability of restoration achievements. The role of WFFG is also important because their households’ income is supported by WFFG and enables the BW CFG members to be more concentrated in maintaining forest sustainability.